KELAYAKAN BUTIR SOAL UNTUK PERMAINAN EDUKATIF PADA MATERI KINGDOM ANIMALIA UNTUK SISWA KELAS X SMA - Fikriyah, Aida (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
An educative game is expected can be used to make students understand more about the concept of sea invertebrate animals. This research aimed to describe the feasibility at some sets of questions to be used as educative game. These sets of questions were validated based on three big components, namely: concept of the topic, the question construction, and language of the question. The questions were validated by biology lecturers and teachers. The validation value of questions was 91.53%. This result showed that all questions were very good and feasible. Key words: educative game, invertebrates, feasibility of the questions.